Administrative Division and Administrative Geography in Hungary - Hajdú, Zoltán (Discussion Papers, 1987)
The study presents major trends of the changing territorial division of Hungarian public administration and the parallel emergence and development of the geography of Hungarian public administration. The Hungarian system of public administration has two histories in reality: 1. the history of the actual public administration 2. the permanent criticism of the prevailing system of public administration, and the history of efforts directed at its reform. An individual part of the study is consecrated to the analysis of spatial relations of public administrative reform plans.